Software Solution for Moving Objects Identification and Tracking Individual Behavior in Studies of Fish Adaptation for Sub-Ambient Temperatures - Berest, Polina (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4):287